PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING BERBANTUAN MEDIA FLASHCARD TERHADAP HASIL BELAJAR IPAS KELAS IV DI SDN 010037 PERKEBUNAN SEI DADAP III/IV T.A 2025/2026 - Amanda Nurul Putri Rambe; Yusra Nasution; Husna Parluhutan Tambunan; Masta Marselina Sembiring; Putra Afriadi (STKIP Subang, 2026)
This study aims to determine the effect of the Problem Solving learning model assisted by Flashcard media on the IPAS learning outcomes of fourth-grade students at SDN 010037 Perkebunan Sei Dadap III/IV. This study employs a quantitative approach with a One Group Pretest-Posttest design. The research sample consisted of 30 fourth-grade students. Data collection was conducted through learning outcome tests. Data analysis used the Shapiro-Wilk normality test, homogeneity test, and hypothesis test. The results of the study show that the average pretest score of 60 increased to 76 in the posttest. The percentage of students' learning completeness also increased from 33.33% to 70%. The hypothesis test results using the Paired Sample T-Test showed a significance value of 0.000 < 0.05, so H0 was rejected and Ha was accepted. Thus, it can be concluded that the Problem Solving learning model assisted by Flashcard media has a positive and significant effect on the science learning outcomes of fourth-grade students at SDN 010037 Perkebunan Sei Dadap IIII/IV.